Evaluation and management of tethered cord syndrome in occult spinal dysraphism: Recommendations from the international children's continence society. Issue 3 (9th August 2017) - Tuite, Gerald F.; Thompson, Dominic N.P.; Austin, Paul F.; Bauer, Stuart B.
Abstract : Aims: As awareness and frequency of tethered spinal cord (TSC) related to occult spinal dysraphism (OSD) has increased with magnetic resonance imaging (MRI), variability exists in its evaluation and management. Due to no published level I data, we summarize the current International Children's Continence Society (ICCS) recommendations for diagnosis and treatment of OSD. Methods: Guidelines were formulated based on analysis of pertinent literature and consensus among authors. This document was vetted by the multidisciplinary members of the ICCS via its website before submission for peer review publication. Results: The more frequent diagnosis of OSD is associated with increased operative intervention. Spinal cord untethering (SCU) has a highly variable risk profile, largely dependent on the specific form of OSD. Progressive neurological deterioration attributed to "tethered cord" may occur, with or without surgery, in selected forms of OSD whereas other cohorts do well. Conclusion: Infants with classic cutaneous markers of OSD, with progressive neurologic, skeletal, and/or urologic findings, present no diagnostic or therapeutic dilemma: they routinely undergo MRI and SCU. Conversely, in asymptomatic patients or those with fixed, minor abnormalities, the risk profile of these OSD cohorts should be carefully considered before SCU is performed. Irrespective of whether or not SCU is performed, patients at risk for progression should be followed carefully throughout childhood and adolescence by a multidisciplinary team.